Age-Related Trends in Body Composition among Women Aged 20-80 Years: A Cross-Sectional Study - Nirmala Rathnayake; Hasanga Rathnayake; Sarath Lekamwasam (Hindawi Limited, 2022)
The determinants of body composition are likely to vary geographically due to the diversity of genetic and environmental factors between populations. Age-related trends in body composition in a population help understanding the health issues that are linked with different body compartments. In general, such studies are scarce in the South Asian region and this cross-sectional study examined the age-related trends in body composition in a selected group of healthy women aged 20-80 years in Sri Lanka. The study included randomly selected 784 healthy women aged 20-80 years from the Southern province, Sri Lanka. Women were divided into five age groups: 20-29 years (n = 79), 30-39 years (n = 144), 40-49 years (n = 185), 50-59 years (n = 281), and ≥60 years (n = 85). Total body bone mineral density (TBBMD, g/cm2), total body bone mineral content (TBBMC, g), total body fat mass (TBFM, kg), and total body lean mass (TBLM, kg) were measured with central-type dual-energy X-ray absorptiometry (DXA). Multivariate analysis of variance with Bonferroni post hoc test was performed. The age-related trends of TBBMD and TBBMC were similar with a peak in 40-49-year age group. Between 50 and 59 and ≥60 age categories, TBBMD and TBBMC showed a rapid decline: 16% and 23%, respectively. The rate of TBBMD decline was 0.008 g/cm2 per year after 50 years. TBFM increased by 14% between age categories 20-29 and 40-49 years and remained unchanged after 49 years. TBLM increased by 15% between age groups 20-29 and 40-49 years and then decreased by 13% between age categories 50-59 and ≥60 years. Of the 13% decrease in TBLM after 50 years, 9% loss occurred after 59 years. The trends observed help to understand the occurrence of diseases linked with body composition.